ANALYSIS OF ICT LITERACY IMPLEMENTATION IN MSME DIGITALIZATION THROUGH QRIS PAYMENT SYSTEM IN INDONESIA - Muhajji, Musdalifah (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
Digital transformation in payment systems has changed transaction behavior among communities and MSMEs. QRIS (Quick Response Indonesian Standard), established by Bank Indonesia as the national standard for QR-based payments, has become a key instrument in accelerating cashless transactions in Indonesia [1]. By October 2023, QRIS reached 29.6 million merchants, of which 92% were MSMEs [2]. This study analyzes ICT literacy implementation in QRIS adoption among MSMEs and its impact on transaction effectiveness and business record-keeping. The research uses a qualitative descriptive approach through document analysis and a conceptual case study by mapping competencies for access, utilization, evaluation, and information security in QRIS use. Results indicate that QRIS adoption requires basic-to-intermediate ICT literacy skills, including operating devices and payment applications, verifying transactions, managing digital payment evidence, and mitigating risks of digital fraud. QRIS contributes to faster transactions, easier recording, and stronger MSME financial inclusion, yet challenges remain due to digital literacy gaps, limited internet infrastructure, and security issues. The study concludes that strengthening ICT literacy through continuous education and assistance is essential to optimize QRIS utilization among MSMEs.